Subcuticular Suturing Versus Vertical Mattress Suture Technique after Open Appendectomy - Haider Ali, Suliman Shah, Tayyeb Ullah, Sidra Jabeen, Muhammad Marwan, Khalid Habib (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Mattress or simple interrupted sutures are the most often used suturing techniques, and they may result in significant scarring. For simple appendicitis, the Steri-StripsTM supported subcuticular suturing approach is advised. Objective: To compare subcuticular suturing versus vertical mattress suture technique after open Appendicectomy. Study Design: Randomized Controlled Trial Setting: Department of General Surgery Lady Reading Hospital, Peshawar. Study Duration: From August 04, 2020 to February 03, 2021. Materials and Methods: A total of 60 patients having acute appendicitis and scheduled for appendectomy were included in the study in a consecutive manner and randomly allocated in two groups. Patients in group A were subjected wounds closure with subcuticular sutures while in group B to sound closure with vertical mattress sutures. All patients were followed to determine the postoperative pain and width of scar. Data analysis was carried out using SPSS V23 Software for Microsoft windows. Results: The mean age of the whole sample was 32.6 + 9.2 years. The mean age in group A was 31.7 + 8.6 years while in group B it was 33.3 + 9.8 years (p 0.512). 66.7% patients in group A were males compared to 53.3% in group B (p 0.292). The mean BMI of group A was 24.2 + 2.2kg/m2 while in group B, it was 24.9 + 2kg/m2 (p 0.169). On follow up, the mean postoperative pain in group A was 1.7 + 0.8 compared to 2.3 + 0.9 in group B (p 0.010). The mean width of scar in group A was 1.6 + 0.6 mm compared to 2.7 + 1.0mm in group B (p < 0.001). Conclusion: Subcuticular suture technique is superior to vertical mattress technique in terms of less postoperative pain and width of scar. However, since our study sample size was small and many effect modifiers / covariates were not addressed in our study, we cannot recommend subcuticular suture technique as routine for wound closure after appendectomy. Keywords: Acute appendicitis; appendectomy; pain; scar; subcuticular sutures